2021
DOI: 10.1155/2021/3119185
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Sociodemographic Characteristics, Psychological Distress, Job Satisfaction, and Their Willingness to Include Children with Special Needs in Regular Classes

Abstract: Advancing inclusive education in countries where children with special needs (CWSNs) are yet to be meaningfully included in regular schools will ensure the progress of Goal 4 of the Sustainable Development Goals. One potent determinant to the effective inclusion of CWSNs is teachers’ intention and efforts to integrate them into their classes. Yet, there is still inadequate evidence in the existing body of literature that will help stakeholders understand the psychosocial variables that will impact their intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 89 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…Teacher willingness to include children with special needs questionnaire (TWICWSNQ) This is a 10-item questionnaire that measures the willing efforts and intentions of regular teachers to accept SEN. Nwosu et al (2020) and Nwosu, Wahl, Oparaugo, et al (2021); Nwosu, Wahl, Cassim, et al (2021) reported that this questionnaire is a combination of the 'Teacher Willingness to Teach Challenging Children Questionnaire (TWTCCQ)' developed by Low et al (2019) and the 'Teachers' Multidimensional Attitude towards Inclusive Education Scale (TMATIES)' developed by Mahat (2008). They reported that the essence of this merger is the understanding that teaching SEN also demands provision of emotional support to these students.…”
Section: Teacher Job Satisfaction Scale (Tjs)mentioning
confidence: 99%
See 4 more Smart Citations
“…Teacher willingness to include children with special needs questionnaire (TWICWSNQ) This is a 10-item questionnaire that measures the willing efforts and intentions of regular teachers to accept SEN. Nwosu et al (2020) and Nwosu, Wahl, Oparaugo, et al (2021); Nwosu, Wahl, Cassim, et al (2021) reported that this questionnaire is a combination of the 'Teacher Willingness to Teach Challenging Children Questionnaire (TWTCCQ)' developed by Low et al (2019) and the 'Teachers' Multidimensional Attitude towards Inclusive Education Scale (TMATIES)' developed by Mahat (2008). They reported that the essence of this merger is the understanding that teaching SEN also demands provision of emotional support to these students.…”
Section: Teacher Job Satisfaction Scale (Tjs)mentioning
confidence: 99%
“…Inclusion willingness for children with SENs has been conceptualized as the intention of the teacher to invest their efforts to align their lessons in such a way that the diversity that may arise from a child with special needs are addressed (Gilor & Katz, 2018a, 2018b). We operationalize it as reflected in teachers' gracious acceptance of children with SENs in such a way that they are ready to conscientiously modify their teaching and provide emotional supports that favour all the learners in their classes (Nwosu, Wahl, Cassim, et al, 2021; Nwosu, Wahl, Oparaugo, et al, 2021). Researchers have in recent times engaged in understanding factors that may impact on the willingness to teach SEN (Gilor & Katz, 2018a, 2018b; Low et al, 2019; Nwosu et al, 2020; Nwosu, Wahl, Cassim, et al, 2021; Nwosu, Wahl, Oparaugo, et al, 2021).…”
Section: Literaturementioning
confidence: 99%
See 3 more Smart Citations